Study Comparing the Shear Bond Forte of Ceramics with Metal Reinforcement to Unreinforced Ceramic Brackets - Asadullah, Hafsa Gul, Syed Wasif Ali Shah, Fawad Fayyaz, Zubair Gul, Muhammad Asim Farooq, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: In an effort to address the growing need for more aesthetic appliances, ceramic brackets were introduced into orthodontics. The need for more aesthetic and less obvious appliances has risen as a result of adult orthodontic therapy. Aim: To assess the shear bond strength of the Clarity and Transcend 6000 brackets as well as the bracket breakdown mechanism while utilising shear force with Schimadzu testing equipment, information from this study will be useful for orthodontic participants as well as practitioners. Methodology: This comparative study was conducted at Orthodontic Department, Bacha Khan College of Dentistry, Mardan from 1st July 2021 to 31st December 2022. A total of 150 brackets (75 reinforced ceramic brackets and 75 conventional ceramic brackets in each cluster) were enrolled. The first premolar teeth that had been pulled in their entirety for orthodontic treatment were chosen to be bonded. Only the first maxillary premolar teeth with undamaged surfaces that had recently been removed and preserved were used. Premolars that had broken down or decayed were eliminated. Result: There was no statistically significant difference amongst the two brackets evaluated, according to an independent t-test associating the clarity and transcends 6000 ceramic brackets. Conclusion: The differences in adhesive remnant index ratings and shear bond forte between the Transcend 6000 ceramic and Clarity were negligible. Key words: Adhesive remnant index (ARI), De-bonding, Shear bond strength